AN ANALYSIS OF NATURALISM IN SEAN BAKER’S MOVIE “THE FLORIDA PROJECT” - Syamsul Bahri; Dinda Aulia Rahmadani; Elmi Sumirah Harahap (Nusantara Hasana Berdikari, 2022)
Naturalism provides appreciation of the world works and encourages learning through identification of models and application of reasoning to problems. The purpose of this study is to explore scenes and dialogues of naturalism, in the movie The Florida Project. The researchers applied the qualitative descriptive research method with the theory of the aspects of naturalism according to Vernon L. Parrington (1927). The subject was the story of The Florida Project. The researchers collected and identified scenes concerning the aspect of naturalism in the movie as the technique. The result showed several aspects of naturalism such as Objectivity, Flippant Disposition Toward Material, Determinism, Inclination Toward Negativity in Choice of Detail, Characters Are Liable to Specific Enticements, Frankness, and Pessimism. Science of naturalism can help humans see reality of life deeply and have broader understanding of the consequences occur in life. The most common aspect is Inclination Toward Negativity in the Choice of Detail. It shows that Halley, the main character tends to show her angry side more often than her calmness. Characters are Liable to Specific Enticements and Pessimism is the least aspect of this movie. Both are related to each other in terms of Halley's recklessness and unseriousness in her life.